1985
DOI: 10.1007/bf00040194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of various media constituents on the growth of Cinchona ledgeriana tissue cultures and the production of alkaloids and anthraquinones therein

Abstract: Using the methods reported by De Fossard et al. (11) the influence of various media constituents on the growth and the alkaloid and anthraquinone production in Cinchona ledgeriana callus cultures was studied. Growth and indole alkaloid production (e.g. cinchonamine) was improved by higher auxin levels. The best growth was observed in the light, although many media resulted in no growth at all in the light. Anthraquinone production was highest at lower auxin levels. Quinoline alkaloid levels (e.g. quinidine) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
3
3
3

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 13 publications
3
24
1
Order By: Relevance
“…The maximum in these spectra at ca. 500 nm was used for the calculations, and alizarin was used as a calibration standard [1].…”
Section: Quantitative Determination Of Anthraquinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum in these spectra at ca. 500 nm was used for the calculations, and alizarin was used as a calibration standard [1].…”
Section: Quantitative Determination Of Anthraquinonesmentioning
confidence: 99%
“…In a recent study we have reported on the influence of various medium components on the growth of C. ledgeriana tissue cultures and the production of secondary metabolites therein [ 1 ]. In that study a cell suspension culture was plated on solid media and, subsequently, growth and secondary metabolite production were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Media containing 0.25, 0.5 and 1 times the normal MS inorganic salt concentration [4] were prepared and 80 cultures of each medium were established. A second group of experiments were designed to determine the most active auxin and cytokinin or cytokinin combination to use for shoot production since different plants respond to different hormones [2]. To evaluate auxins, indoleacetic acid (IAA), indolebutyric acid (IBA), or NAA were added at 0.5 or 5.0pM to the MS medium.…”
Section: Methodsmentioning
confidence: 99%
“…Several elicitors are being employed in in vitro cultures of plants for the increased production or induced de novo synthesis of secondary metabolites (Sudha and Ravishankar 2003a;Karuppusamy 2009). For example, 2,4-dichlorophenoxy acetic acid (2,4-D), indole acetic acid (IAA), and naphthalene acetic acid (NAA) have increased the production of indole alkaloids in cell cultures of Cinchona ledgeriana (Harkes et al 1985). Half-strength Gamborg's B 5 medium supplemented with 5 % sucrose and 1 mg/l of each of NAA and BA gave the best values in root culture growth of Datura candida x D. aurea (Nussbaumer et al 1998), whereas full-strength B 5 medium supplemented with the same concentrations of NAA and BA gave the best results for hyoscyamine and scopolamine content.…”
Section: Elicitationmentioning
confidence: 99%